THE WORKING ACTIVITY IN THE MANIFESTATIONS OF SPECIFICATIONS OF MONEY ATTITUDE AND ITS PERCEPTION - Hayrapetyan , D. R.; Amiraghyan , A. V. (Modern Psychology, 2019)
People greatly differ in their perception of money and money attitude. According to different researches they are formed under the influence of certain factors, among which have been separated and studied the following ones: person’s age, gender, personal and socio-cultural peculiarities, person’s income level etc. Each of these factors forms certain standpoints towards money. As the main means of acquiring money is considered to be the work, in this research we have studied person’s work performance in the manifestation of money attitude and its perception specifications. Moreover, the aspiration for acquiring money is especially obvious in today’s youth. So this article is directed to do a research about the money attitude and its perception specifications among the young students who either have or have not a working activity.
Keywords: financial behavior, labor activity, money attitude, money perception.